2020
DOI: 10.1186/s12998-020-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of spinal manipulation on the pressure pain threshold in young, asymptomatic subjects? A randomized placebo-controlled trial, with a cross-over design

Abstract: Background: Spinal manipulation (SM) has been shown to have an effect on the pressure pain threshold (PPT) in asymptomatic subjects, but SM has never been compared in studies on this topic to a validated sham procedure. We investigated the effect of SM on the PPT when measured i) in the area of intervention and ii) in an area remote from the intervention. In addition, we measured the size and duration of the effect. Method: In a randomized cross-over trial, 50 asymptomatic chiropractic students had their PPT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Our results do not suggest that a single spinal HVLA technique may specifically activate the descending pain inhibitory system projecting from the periaqueductal gray matter since we found (i) no effect on local and distal PPT [31] and (ii) no effect on cardiovascular autonomic outcomes. In addition, we found (iii) no relationship between PPT and autonomic responses after the HVLA technique.…”
Section: Implication and Perspectivescontrasting
confidence: 83%
See 1 more Smart Citation
“…Our results do not suggest that a single spinal HVLA technique may specifically activate the descending pain inhibitory system projecting from the periaqueductal gray matter since we found (i) no effect on local and distal PPT [31] and (ii) no effect on cardiovascular autonomic outcomes. In addition, we found (iii) no relationship between PPT and autonomic responses after the HVLA technique.…”
Section: Implication and Perspectivescontrasting
confidence: 83%
“…Please note that another report deals with the assessment of the specific effect of the spinal manipulation on pressure pain threshold [31].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this consensus on segmental effects of SM, it should be noted that two recent studies using a single‐blinded placebo‐controlled design obtained conflicting results (Aspinall et al., 2019; Honore et al., 2020). The quality of studies on segmental hypoalgesia resulting from SM is variable.…”
Section: Mechanisms Of Pain Relief By Smmentioning
confidence: 99%
“…Nevertheless, a question that remains unanswered is whether these placebo interventions lack any therapeutic effects (Chaibi et al., 2015; Vernon et al., 2012). Indeed, these placebo interventions allowed successful blinding, but reported no significant group difference (Aspinall, Jacques, et al., 2019; Honore et al., 2020). This was interpreted as a lack of therapeutic effect of SMT, but it could be argued that the placebo intervention may not be inert and may have masked therapeutic effects.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…However, a recent systematic review on whether SMT can be used to prevent or treat non-MSK disorders has shown that SMT appears to be useful but only in methodologically weak studies, whereas, in the properly conducted studies, SMT did not come out better than sham or no treatment, regardless the condition that was treated [ 4 ]. Two recent systematic reviews did not support the concept that SMT would be beneficial on the autonomic nervous system [ 5 , 6 ], neither did a more recent randomized control trial with a successful sham [ 7 ]. As for the therapeutically beneficial effect of SMT on the brain, a recent systematic review of RCTs on the subject failed to reveal any positive evidence [ 8 ].…”
Section: Introductionmentioning
confidence: 99%